Scrutinizing Sustainability Change and Its Institutionalization in Organizations - Lozano, Rodrigo; Garcia, Iciar (Frontiers in Sustainability, 2020)
Organisations (i.e. civil society, corporations, and public sector organisations) have been instrumental in driving sustainability. In the last decade, there has been an increasing interest in organisational sustainability, and an increase of organisational change management for sustainability. Although, there have been many efforts aimed at incorporating sustainability in organisations, incorporating, integrating, and institutionalising sustainability in organisations is still under-researched. A survey was developed for investigating the importance of how sustainability has been embedded in organisations’ system elements. The survey was sent to a database of 5,299 contacts from different organisations worldwide. From the total, 281 useable responses (6.78%) for the organisational change part were obtained. The variables analysed were mainly ordinal scales, therefore, non-parametric methods were used for the analyses, including descriptive, Friedman test for ranking, and Kruskal Wallis and Wilcoxon tests for comparisons. More than 90% of the responding organisations have been working with sustainability for more than five years. The main driving forces for sustainability have been motivated equally by external stimuli and internal factors. The focus on sustainability and recognition of the impacts that the organisation has are fairly aligned. The findings show that the main areas, from the start and during the changes, have been on governance, management and strategy, and operations and production. The majority of the changes were effected between six and seven systems elements, which indicates a large degree of institutionalisation. The comparison tests show that the nature of the organisation plays a key role for where the sustainability changes start, and how the changes affect system elements. The research highlights that it inconsequential where sustainability changes start, as long as sustainability is adopted throughout all the system elements, including internal and external stakeholders. Planning sustainability changes must address its four dimensions holistically, as well as technical, managerial, and organisational issues, and the organisation’s stakeholders.